Insomnia in traditional Persian medicine : Insomnija u tradicionalnoj perzijskoj medicini - Nimrouzi, Majid (Array, 2019)
Insomnia is a common complaint in outpatient clinics. It usually affects quality of life negatively, especially in severe cases. Nowadays, routine medical interventions comprise pharmacological approaches and cognitive behavioral therapy. Common medications used by afflicted patients are not competent enough in addition to their annoying side effects. It would naturally denote the need for considering novel strategies for treating insomniac patients. Approach to insomnia in traditional Persian medicine (TPM) has been cited in a scrutinized manner focusing on its main causes. Accordingly, its treatment is tailored based on the constitution of the patient, intensity of the disease, and type of the cause. In this paper we have discussed the causes of insomnia, diagnostic approach, and various medical interventions proposed in valid sources of TPM.